Mutual fund insurance - Gatto, Mary Ann; Geske, Robert; Litzenberger, Robert; Sosin, Howard (Journal of Financial Economics, 1980)
During the 1970's, mutual fund insurance was sold in the U.S. by the Harleysville and Prudential Insurance Companies. This paper examines the valuation and demand for this insurance. It illustrates that because of its design, for many plausible combinations of model parameters, a competitive premium need not exist for the Harleysville contract. A competitive premium will always exist for the Prudential policy, however the value is directly related to the age of the purchaser. Harleysville charged the same premium to all funds and therefore was subject to adverse selection. Evidence of this effect is provided by illustrating that the demand for the insurance was directly related to its competitive market value.